Encyclopedia of Life Sciences 2013
DOI: 10.1002/9780470015902.a0024406
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Primary Biliary Cirrhosis

Abstract: Primary biliary cirrhosis (PBC) is an autoimmune liver disease affecting 0.1% of women over the age of 40 years. PBC is characterised by autoreactive T‐cells and B‐cells specific for mitochondrial self‐antigens, typically the E2‐domain of pyruvate dehydrogenase complex (PDC‐E2), which mediate progressive destruction of the small, intrahepatic bile ducts, eventually leading to cirrhosis. It is believed that environmental factors trigger loss of immune tolerance to PDC‐E2 in those individuals with a genetic pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…GWAS, genome-wide association study; iCHIP, Illumina immunoarray association study; OR, odds ratio; RA, risk allele; SNV, single nucleotide variant. Adapted from Mells and Hirschfield [112] . …”
Section: Figmentioning
confidence: 99%
“…GWAS, genome-wide association study; iCHIP, Illumina immunoarray association study; OR, odds ratio; RA, risk allele; SNV, single nucleotide variant. Adapted from Mells and Hirschfield [112] . …”
Section: Figmentioning
confidence: 99%
“…The incidence of PBC in the UK is 32.2 per 100 000,1 with approximately 20 000 people presently affected. Incidence is higher in females compared with males (10:1) and in the fifth and sixth decade of life such that a woman over 40 years of age has a 1/1000 chance of having this condition 2. While early natural history studies suggested that life expectancy from time of diagnosis was less than 10 years,3 this is no longer true.…”
Section: Introductionmentioning
confidence: 99%